Primary care visits due to injuries among the Aboriginal off-reserve population of British Columbia, Canada, 1991–2010 - Jin, Andrew; George, M. Anne; Brussoni, Mariana; Lalonde, Christopher E.; McCormick, Rod (International journal for equity in health, 2015)
Background Aboriginal people in British Columbia (BC) have higher injury incidence than the general population. This report describes variability in visits to primary care due to injury, among injury categories, time periods, geographies, and demographic groups. Methods We used BC’s universal health care insurance plan as a population registry, linked to practitioner payment and vital statistics databases. We identified Aboriginal people by insurance premium group and birth and death record notations. Within that population we identified those residing off-reserve according to postal code. We calculated crude incidence and Standardized Relative Risk (SRR) of primary care visit due to injury, standardized for age, gender and Health Service Delivery Area (HSDA), relative to the total population of BC. Results During 1991 through 2010, the crude rate of primary care visit due to injury in BC was 3172 per 10,000 person-years. The Aboriginal off-reserve rate was 4291 per 10,000 and SRR was 1.41 (95 % confidence interval: 1.41 to 1.42). Northern and non-metropolitan HSDAs had higher SRRs, within both total BC and Aboriginal off-reserve populations. In every age and gender category, the HSDA-standardized SRR was higher among the Aboriginal off-reserve than among the total population. For all injuries combined, and for the categories of trauma, poisoning, and burn, between 1991 and 2010, crude rates and SRRs declined substantially, but proportionally more rapidly among the Aboriginal off-reserve population, so the gap between the Aboriginal off-reserve and total populations is narrowing, particularly among metropolitan residents. Conclusions These findings corroborate our previous reports regarding hospitalizations due to injury, suggesting that our observations reflect real disparities and changes in the underlying incidence of injury, and are not merely artefacts related to health care utilization.